Environmental Impact of C Excavation Mining Activities in Banyakan District - Romadhon Romadhon; Salwa Nabilah (Litbang Pemas - Universitas Islam Lamongan, 2021)
C Excavation mining activity in Banyakan District, Kediri Regency has been going on for a long time. It is needed to support the creation of good infrastructure and become one of the foundations for development progress, but in its implementation it must pay attention to the preservation of the natural environment. This study uses descriptive analysis method with a quantitative approach, and uses survey and interview methods for data collection. Afterward, the survey data were analyzed by non-parametric test using the free K-sample test, validity and reliability tests, and quantitative analysis using the Analytical Hierarchy Process (AHP) method. Thereafter, with expert recommendations, a strategy for managing the impact was developed. The results of the discussion found that environmental damage due to C excavation activities that often occur and has a major impact in Tiron Village, Banyakan District, includes damage to road infrastructure, air pollution due to material transport vehicle traffic, and loss of rural feel. Therefore, all parties must work together to overcome this, several responses that can be taken to deal with these impacts include all parties having to allocate special funds for road infrastructure improvements, policies from the government that are in favor of the community and the environment, and reclamation of mining former lands to restore a rural feel and good air quality standards